Sistem Informasi Pembayaran Uang Sekolah Pada Sekolah Menengah Atas Negeri 2 Kampung Rakyat Berbasis Web - Safitri, Ria (Universitas Labuhanbatu, 2021)
The progress and development of information technology is currently very rapid. Likewise, the world of education should also always experience development. Kampung Rakyat 2 Senior High School (SMA) is one of the schools that still uses manual means in paying school fees. Payment of school fees is an activity carried out every once a month that is charged to students, where the money will be used to pay salaries for honorarium teachers and other needs. Data collection methods used are observation, interview, and literature study. And using the UML system design method Diagram (Use Case Diagram, Activity Diagram, Sequence Diagram and Class Diagram), with database design and designing interface menus. The programming used is website programming using MySQL and PHP databases. This research resulted in a web-based school payment information system for Kampung Rakyat 2 High School. Hopefully with this information system can simplify and shorten the work of officers, so the process of entering data on payment of school fees can be completed in a short time.